A Geopolitics of the Horse in Finland. Issue 4 (1st October 2016) - Raento, Pauliina
ABSTRACT: The disregard of animal subjectivity in geopolitics is challenged as outdated and arrogant in light of the growing interdisciplinary understanding of the relational, dispersed, and co-evolving nature of agency. First, the war horse is examined by joining the instrumental approach of military history with the emphasis on emotion in animal studies. Knowledge about animal subjectivity is expanded by demonstrating how the horse itself has co-produced the Finnish experience in World War II and the national narrative about this conflict. Calculable territory, biopolitical state intervention, the political ecology of war, affect, and the body build connections between the horse's war and theory, methodology, and concepts in political geography and geopolitics. Equine labour and response to the state's geopolitically motivated breeding exercises during peace then bridge animal studies and critical geopolitics, showing how the horse has supported the formation of Finnishness. Finally, a look at contemporary mobility, geopolitics of disease, and biometric bordering exemplifies how the horse continues to adapt to new roles in Finnish society and contribute to human institutions and governance. The examination demonstrates the importance of other-than-human beings in the making of Finland as a political space and place. Suggestions for further studies and data point to opportunity. The article serves those who question rigid categorisations and segmentation of research and pedagogy into intellectually self-contained islands.